FUTURE RESEARCH IN THE PSYCHOLOGICAL CONTEXT - Chomeya, Rungson; Phansri, Gunniga; Lebkhao, Dussadee; Choompunuch, Bovornpot; Yurayat, Phamornpun; Sariwat, Lakkana; Suk-erb, Wipanee; Tuklang, Supachai; Piyakul, Araya (Journal of Education and Innovation, 2025)
In an era marked by rapid and uncertain change, future research plays a crucial role in forecasting and planning. This research encompasses exploring various possible trends and scenarios, helping stakeholders prepare and adapt to potential changes. Tools such as scenario analysis and trend analysis are used to create diverse and actionable future images. Future research is also significant in psychology, particularly in forecasting the impacts of new technologies on mental states and human behavior, including changes in belief systems and social behavior. Thus, future research is a valuable tool for preparing and developing strategies to address future challenges.